1988
DOI: 10.1128/iai.56.11.2794-2800.1988
|View full text |Cite
|
Sign up to set email alerts
|

Strain variation in phagocytosis of Cryptococcus neoformans: dissociation of susceptibility to phagocytosis from activation and binding of opsonic fragments of C3

Abstract: Phagocytosis of Cryptococcus neoformans is markedly influenced by the presence of a polysaccharide capsule.We examined activation and binding of C3 fragments to eight isolates of C. neqformans. All isolates were shown to have capsules by light and electron microscopy. These strains differed in susceptibility to phagocytosis by neutrophils. Yeast cells were opsonized by incubation in normal human serum. Five strains were resistant to ingestion, two strains showed intermediate levels of resistance to ingestion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 32 publications
(45 reference statements)
4
39
1
Order By: Relevance
“…Almost two decades ago it was reported that C. neoformans strains differed in their ability to be phagocytozed in the presence of serum but this phenomenon remains unexplained 2729. In this study we demonstrate an inverse association between capsule volume and complement‐mediated phagocytosis.…”
Section: Introductionsupporting
confidence: 54%
“…Almost two decades ago it was reported that C. neoformans strains differed in their ability to be phagocytozed in the presence of serum but this phenomenon remains unexplained 2729. In this study we demonstrate an inverse association between capsule volume and complement‐mediated phagocytosis.…”
Section: Introductionsupporting
confidence: 54%
“…Incubation of encapsulated cryptococci in normal human serum leads to activation of the alternative complement system and deposition of potentially opsonic fragments of C3 at the capsular surface and in the capsule interior (Kozel et al ., 1988; 1989). In an effort to assess the extent to which C3 penetrates to the capsule interior, encapsulated cryptococci were incubated for 30 min in 40% NHS, washed with PBS, and the sites of C3 binding were determined by immunofluorescence using fluorescein isothiocyanate (FITC)‐labelled Fab fragments of polyclonal C3 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…When C3 localizes deep inside the capsule, as occurs for cryptococcal cells with large capsules, C3 is not accessible to the receptor and the process is inefficient in promoting phagocytosis (Zaragoza et al ., 2003). Consequently, the efficiency of C‐mediated phagocytosis is critically dependent on the size of the capsule of the C. neoformans strain (Mitchell and Friedman, 1972; Kozel et al ., 1988b; Small and Mitchell, 1989; Yasuoka et al ., 1994; Zaragoza et al ., 2003). Recent studies show that another factor that influences C3 localization is the source of serum, with serum from different mammalian species in different regions of the capsule (Gates and Kozel, 2006).…”
Section: Introductionmentioning
confidence: 99%